Journalism : principles and practice - Harcup, Tony (New Delhi : SAGE Publishing, 2024)
"A textbook that explains the basic concepts of journalism using examples and stories from real life. Journalism: Principles and Practice is an essential textbook that tells us about the theory and practice of journalism. This edition covers new topics that are relevant to today's social media, the rights and wrongs of journalism, and digital media among others. It helps the reader to develop the necessary skills to become a modern ethical journalist. The book gives a complete introduction to the fundamental concepts of journalism through entertaining stories and examples from the newsroom. It will be useful to students who are beginning to explore the world of journalism as well as those seeking to gain a deeper understanding of the basic concepts. Key Features -- Updated with contemporary topics such as social media and new methods of gathering information -- Simple and clear explanations of the basic concepts of journalism -- Relates theory to the real world through exercises that encourage students to think critically -- Contains skills and tips from practicing journalists that help students become industry-ready"--